Tuning synaptic transmission in the hippocampus by stress: the CRH system - Chen, Yuncai; Andres, Adrienne; Frotscher, Michael; Baram, Tallie Z. (Frontiers in Cellular Neuroscience, 2012)
To enhance survival, an organism needs to remember—and learn from—threatening or stressful events. This fact necessitates the presence of mechanisms by which stress can influence synaptic transmission in brain regions, such as hippocampus, that subserve learning and memory. A major focus of this series of monographs is on the role and actions of adrenal-derived hormones, corticosteroids, and of brain-derived neurotransmitters, on synaptic function in the stressed hippocampus. Here we focus on the contribution of hippocampus-intrinsic, stress-activated CRH-CRH receptor signaling to the function and structure of hippocampal synapses. Corticotropin-releasing hormone (CRH) is expressed in interneurons of adult hippocampus, and is released from axon terminals during stress. The peptide exerts time- and dose-dependent effects on learning and memory via modulation of synaptic function and plasticity. Whereas physiological levels of CRH, acting over seconds to minutes, augment memory processes, exposure to presumed severe-stress levels of the peptide results in spine retraction and loss of synapses over more protracted time-frames. Loss of dendritic spines (and hence of synapses) takes place through actin cytoskeleton collapse downstream of CRHR1 receptors that reside within excitatory synapses on spine heads. Chronic exposure to stress levels of CRH may promote dying-back (atrophy) of spine-carrying dendrites. Thus, the acute effects of CRH may contribute to stress-induced adaptive mechanisms, whereas chronic or excessive exposure to the peptide may promote learning problems and premature cognitive decline.